TESTING WEAK FORM OF EFFICIENT MARKET HYPOTHESIS ON SOCIALLY RESPONSIBLE INDICES: COMPARATIVE STUDY BETWEEN DEVELOPED AND EMERGING MARKETS - Mondal, Sabyasachi; Singh, Ranjit; Yadav, Vibha (International Journal of Accounting & Finance Review, 2022)
The study attempts to identify the presence of randomness in the socially responsible indices (SRI) of the stock markets of developed and emerging economies. 9 developed and 5 emerging economies were considered for the test of randomness on daily, weekly, monthly, quarterly and semiannual return of socially responsible and their benchmark indices. The Shapiro-Wilk test is used to test the data's normality, whereas the runs test and Augmented Dickey-Fuller test are used to find the randomness of the data. It has been observed that the market could be more efficient and random for all time durations. Most of the non-randomness is seen in daily and weekly returns. However, inefficiency disappears as the time frame increases. The combination of runs and ADF tests show that South Africa, Singapore, and South Korea show randomness for all time durations, whereas the same randomness pattern for Brazil, Australia, Japan, Singapore, and South Korea. Arab, Austria, Germany, Nordic, and USA are not present in daily return and randomness for all other durations for both the test combinations. India and Egypt show non-randomness in daily and weekly returns and randomness for all other durations under the first test combination. It is also observed that most socially responsible investment indices resonate with the randomness patterns of benchmark indices. Socially responsible investors such as pension funds may find the article resourceful in identifying socially responsible investment destinations and diversifying their portfolios.JEL Classification Codes: G32, F65, L66, L25, M41.